Bioactive Properties of Fermented Beverages: Wine and Beer - Vanesa Postigo; Margarita García; Julia Crespo; Laura Canonico; Francesca Comitini; Maurizio Ciani (Fermentation)
In recent years, consumer demand has been increasingly oriented to fermented foods and/or beverages with functional properties. The functional beverage industry focused on producing a product that combines a peculiar aromatic taste with healthy properties. Today’s consumers are trying to reduce alcohol, gluten, sugar, and carbohydrates in beer and wine without reducing their native taste. Wine and beer are among the world’s most consumed beverages, and several studies confirm that fermented beverages could be associated with beneficial properties for human health. All beneficial properties derive both from the fermentation process and also from the characteristics of the raw materials used in the two beverages. This review was conducted to highlight the importance of the fermentative microorganisms in wine and beer and their relationship with functional foods, underlining their involvement in human health.